Comparative Experimental Study on Calcium Oxide, Calcium Hydroxide, and Calcium Carbonate Solidified Zinc-Contaminated Red Clay. (7th April 2022) - Song, Yu; Li, Hui; Gan, Xiaohui; Zhang, Mingzhi; Xue, Mingming; Li, Jun
Abstract : Calcium oxide is a common curing agent used for curing contaminated soils. It is often used with cement to adjust the pH value. Calcium carbonate and calcium hydroxide are common products of calcium oxide. The effects of three kinds of binder in curing Zn 2+ -contaminated red clay are compared. The Zn 2+ concentrations were selected as 0.1 and 0.5%, and the curing agent was added separately. The values of the unconfined strength of soil samples were compared after the three curing agents were added to the soil alone. It was found that the strength of the specimen with the addition of calcium carbonate was lower than the strength of the contaminated soil without the addition of the curing agent, while the strength of calcium hydroxide and calcium oxide was enhanced with the addition of calcium hydroxide, in general, and the strength of calcium oxide was higher. When CaO is added, the strength of the sample with a 0.1% concentration of zinc-contaminated soil is greater than the strength of the sample with a 0.5% concentration. But when Ca(OH)2 is added, the strength of the sample with 0.1% zinc-contaminated soil is less than the strength of the sample with a 0.5% concentration. Ca(OH)2 provides enough OH -, and there are enough zinc ions to react with it in the high-concentration Zn 2+ -contaminated soil to form CaZn2 (OH)6 ·2H2 O, which enhances the strength of the soil. By comparing the pH values of calcium oxide and calcium hydroxide, the pH of the soil is about 12, and the pH of calcium carbonate is about 8.